Intestinal Permeability Measured by Urinary Sucrose Excretion Correlates with Serum Zonulin and Faecal Calprotectin Concentrations in UC Patients in Remission - C. A. M. Wegh; N. M. de Roos; R. Hovenier; J. Meijerink; I. Besseling-van der Vaart; S. van Hemert; B. J. M. Witteman (Journal of Nutrition and Metabolism)
Background and Aims. Ulcerative colitis (UC) is associated with an increased intestinal permeability, possibly through a dysbiosis of intestinal bacteria. We investigated which markers are most relevant to assess intestinal permeability in UC patients and whether probiotics had an effect on these markers. Methods. In this twelve-week placebo-controlled randomized double-blind study, twenty-five subjects with UC in remission received either placebo or a multispecies probiotics. Samples of blood, urine, and faeces were taken at baseline, week 6, and week 12 to assess intestinal permeability and inflammation. Diaries and Bristol stool scale were kept to record stool frequency and consistency. Quality of life was scored from 32–224 with the inflammatory bowel disease questionnaire (IBD-Q). Results. This group of UC patients, in clinical remission, did not show increased intestinal permeability at baseline of this study. During the study, no significant group or time effects were found for intestinal permeability measured by the 5-sugar absorption test, serum zonulin, and faecal zonulin. Likewise, the inflammatory markers C-reactive protein (CRP), calprotectin, and the cytokines IFNγ, TNFα, IL-6, and IL-10 were not significantly affected. Stool frequency and consistency were not significantly affected either. The IBD-Q score, 194 for the probiotics group and 195 for the placebo group, remained unaffected. Correlations were tested between all outcomes; urinary sucrose excretion was significantly correlated with serum zonulin (r = 0.62) and faecal calprotectin (r = 0.55). Faecal zonulin was not significantly correlated with any of the other markers. Conclusion. Serum zonulin may be a more relevant biomarker of intestinal permeability than faecal zonulin, due to its correlation with other biomarkers of intestinal permeability. UC patients in remission did not show an effect of the probiotic treatment or a change in gut permeability. This should not discourage further studies because effects might be present during active disease or shortly after a flare up.